Communication Channels and Word of Mouth: How the Medium Shapes the Message - Berger, Jonah; Iyengar, Raghuram (Journal of Consumer Research, 2013)
Consumers share word of mouth face to face, over social media, and through a host of other communication channels. But do these channels affect what people talk about and, if so, how? Laboratory experiments, as well as analysis of almost 20,000 everyday conversations, demonstrate that communicating via oral versus written communication affects the products and brands consumers discuss. Compared to oral communication, written communication leads people to mention more interesting products and brands. Further, this effect is driven by communication asynchrony and self-enhancement concerns. Written communication gives people more time to construct and refine what to say, and self-enhancement motives lead people to use this opportunity to mention more interesting things. These findings shed light on how communication channels shape interpersonal communication and the psychological drivers of word of mouth more broadly.